Деформационное упрочнение стали с бейнитной структурой - Громов, В.Е.; Никитина, Е.Н.; Иванов, Ю.Ф.; Аксёнова, К.В.; Корнет, Е.В. (Успехи физики металлов, 2015)
Методами просвечивающей электронной дифракционной микроскопии выполнен количественный анализ эволюции дефектной и карбидной подсистем среднеуглеродистой стали с бейнитной структурой при деформации сжатием до 36%. Выполнен количественный анализ перераспределения углерода и установлены зависимости концентрации атомов углерода, расположенных в кристаллической решётке α- и γ-железа, на дефектах структуры, в цементитных частицах, лежащих в объёме пластин бейнита и на внутрифазных границах, от степени деформации. Определены зависимости продольных и поперечных размеров частиц цементита в объёме кристаллов бейнита, объёмных долей частиц цементита и остаточного аустенита, скалярной плотности дислокаций, объёма материала с микродвойниками, размеров фрагментов, количества концентраторов напряжений и ширины контуров экстинкции от степени деформации. Показано, что с ростом степени деформации скалярная плотность дислокаций, объём материала с деформационными двойниками, количество концентраторов напряжений, амплитуда кривизны–кручения кристаллической решётки, степень разориентации фрагментов увеличиваются, а средние продольные размеры фрагментов — уменьшаются. Выполнена оценка дальнодействующих полей напряжений. Обсуждены возможные причины стадийности изменения параметров карбидной фазы и дислокационной субструктуры с деформацией. Проведены оценки механизмов упрочнений границами пластин и фрагментов, скалярной плотностью дислокаций, дальнодействующими полями напряжений, частицами цементита, атомами внедрения. Показано, что наибольший вклад в величину деформационного упрочнения исследуемой стали даёт субструктурное упрочнение (упрочнение, обусловленное дальнодействующими внутренними полями напряжений и фрагментацией структуры) и твёрдорастворное упрочнение, обусловленное внедрением атомов углерода в кристаллическую решётку феррита. Высказано предположение, что причиной разупрочнения стали с бейнитной структурой при больших (более 15%) степенях деформации является активация процесса деформационного микродвойникования. Методами просвітлювальної електронної дифракційної мікроскопії виконано кількісну аналізу еволюції дефектної та карбідної підсистем середньовуглецевої криці з бейнітною структурою при деформації стисненням до 36%. Виконано кількісну аналізу перерозподілу Карбону і встановлено залежності концентрації атомів Карбону, розташованих у кристалічній ґратниці α- і γ-заліза, на дефектах структури, у цементитних частинках, що лежать в об’ємі платівок бейніту та на внутрішньофазових межах, від ступеня деформації. Визначено залежності поздовжніх і поперечних розмірів частинок цементиту в об’ємі кристалів бейніту, об’ємних часток частинок цементиту і залишкового аустеніту, скалярної густини дислокацій, об’єму матеріялу з мікродвійниками, розмірів фраґментів, кількости концентраторів напруг і ширини контурів екстинкції від ступеня деформації. Показано, що з ростом ступеня деформації скалярна густина дислокацій, об’єм матеріялу з деформаційними двійниками, кількість концентраторів напруг, амплітуда кривини–скручування кристалічної ґратниці, ступінь дезорієнтації фраґментів збільшуються, а середні поздовжні розміри фраґментів — зменшуються. Виконано оцінку далекосяжних полів напружень. Обговорено можливі причини стадійности зміни параметрів карбідної фази і дислокаційної субструктури з деформацією. Проведено оцінювання механізму зміцнення межами платівок і фраґментів, скалярною густиною дислокацій, далекосяжними полями напружень, частинками цементиту, атомами втілення. Показано, що найбільший внесок у величину деформаційного зміцнення досліджуваної криці дає субструктурне зміцнення (зміцнення, зумовлене далекосяжними внутрішніми полями напруг і фраґментацією структури) та твердорозчинне зміцнення, зумовлене втіленням атомів Карбону в кристалічну ґратницю фериту. Висловлено припущення, що причиною знеміцнення криці з бейнітною структурою за великих (більших за 15%) ступенів деформації є активація процесу деформаційного мікродвійникування. The analysis of constructional steel 30Cr2Ni2MoV (in mass %: C—0.3; Cr ≤ 2; Ni ≤ 2; Mo ≤ 1; V v 1, Fe—the rest) under compression up to fracture after air cooling from the austenisation temperature of 960°C is carried out. Two stages of deformation strengthening are revealed: 1st stage with the parabolic σ(ε) dependence and decreasing coefficient of deformation strengthening; 2nd stage with the weakly changing negative strengthening coefficient. Using the methods of transmission electron diffraction microscopy, a quantitative evolution analysis of the defect and carbide subsystems of this medium-carbon steel with a bainite structure under compression strain up to 36% is performed. A quantitative analysis of the carbon redistribution is also performed, and the dependences of the concentration of carbon atoms arranged in a crystal lattice of the α- and γ-irons, on the structural defects, in cementite particles lying in the bulk of bainite plates and in-phase boundaries, on the deformation degree. The dependence of the longitudinal and cross-sectional dimensions of cementite particles in bainite crystals, volume fractions of cementite particles and retained austenite, the scalar density of dislocations, the material volume with microtwins, fragment size, the number of stress concentrators, and the width of the extinction contours on the deformation degree is determined. As shown, the scalar dislocation density, the material volume with deformation twins, the number of stress concentrators, the curvature–torsion amplitude of a crystal lattice, disorientation degree of fragments are increasing with growing deformation degree, and average longitudinal fragment sizes are decreasing. The long-range stress fields are estimated. The possible causes of the staging of changes of the carbide-phase and dislocation-substructure parameters with deformation are discussed. As shown, the carbide transformations in the bainite structure are occurring in course of two competition processes: dissolution of cementite particles being formed in ferrite plates during bainite transformation and their precipitation at the dislocation-substructure elements during ‘deformation ageing’. Simultaneously, the additional transformation of retained austenite initiated by steel deformation is observed. As shown, the transition from the first stage of steel deformation to the second one is prepared by the following modifications of the structural-phase state of the material: firstly, by the completion of the process of intensive dislocation accumulations; secondly, by the initiation of the mechanism of the deformation microtwins; thirdly, by the completion of the fragmentation process of bainite plates; fourthly, by the maximum density of flexural extinction circuits; fifthly, by the substantial increase in solid-solution steel hardening. As a whole, all these processes lead to the formation of the areas in the material with a critical substructure capable of the microcrack formations with the subsequent destruction of the sample. Strengthening mechanisms with the boundaries of plates and fragments, the scalar dislocation density, long-range stress fields, cementite particles, interstitial atoms are estimated. As shown, the largest contribution to the work hardening of the investigated steel is given by the substructural hardening (hardening due to the long-range internal-stress fields and fragmentation patterns) and solid-solution hardening, due to the introduction of carbon atoms into the crystal lattice of the ferrite. As suggested, the cause of softening of steel with a bainite structure at high (over 15%) degrees of deformation is the activation of the process of deformation fine-scale twinning.